Aeolian transport of seagrass (Posidonia oceanica) beach-cast to terrestrial systems. (5th September 2017) - Jiménez, Maria A.; Beltran, Rafel; Traveset, Anna; Calleja, Maria Ll; Delgado-Huertas, Antonio; Marbà, Núria
Abstract: The annual export of the Mediterranean seagrass ( Posidonia oceanica ) litter to adjacent beaches and coastal dunes was quantified by examining the fortnight evolution of seagrass beach-cast volume on two beaches in the NW Mediterranean (Son Real and Es Trenc, Mallorca Island, Spain) for two years and analyzing the wind speed and direction obtained from the closest Meteorological Spanish Agency surface weather stations. The decomposition stage of the deposits was examined by analyzing the total hydrolysable amino acids, its percentage distribution and derived degradation indexes. Prevalent winds exceeding 6 m s −1, the coastline morphology and type of terrestrial vegetation determine the annual dynamics of the seagrass beach-cast. In the most protected beach (Son Real) the seagrass beach-cast remained nearly stationary during the two studied years while it exhibited wide annual fluctuations in the less protected one (Es Trenc). The amounts of P. oceanica wrack washed on Son Real and Es Trenc beaches, respectively, were estimated at 309 kg DW m coastline −1 yr −1 and 1359 kg DW m coastline −1 yr −1 . They supplied between 20 kg CaCO3 m coastline −1 yr −1 and 47 kg CaCO3 m coastline −1 yr −1 . Between 54% (Son Real) and 70% (Es Trenc) of seagrass beach-cast, respectively accounting for 1.5 kg N m coastline −1 yr −1 and 8.6 kg N m coastline −1 yr −1, were annually exported from the beaches to adjacent dune systems. Our results reveal that Mediterranean seagrass meadows might be an important source of materials, including sand and nutrients, for adjacent terrestrial systems, able to support their functioning. Graphical abstract: Image 1 Highlights: The annual evolution of the seagrass beach-cast depends on the beach exposure. Changes of the seagrass beach-cast are linked to strong wind events. Winds are the responsible of the mass transport of nutrients to the dunes. Beach-cast deposits might be an important source of carbonates and nutrients to the coastal dune system.